Introduction to Drinking Water Quality Standards for Communities in Poka Village, Teluk Ambon District - Rumpakwakra, Ervina; Hattu, Nikmans; Jaya, Gede Wiratma; Nggolaon, Delpina; Rikumahu, Marcia Violetha; Thohirah, Afifah; Silahooy, Stevi; Latupeirissa, Jolantje; Telussa, Ivonne; Pada, Samuel Simra; Kololu, Micky (Universitas Mataram, 2024)
The quality of clean water used has been a top priority to maintain health and fulfill daily needs. There are many sources of clean water, including well water, bottled water, gallon water and PDAM water. The use of clean water in Poka Village still uses well water and gallon water, so there is concern among the community regarding the cleanliness and quality of the water. Therefore, this service is carried out to help answer public anxiety by introducing Drinking Water Quality Standards that have been determined in the Republic of Indonesia Minister of Health Regulation No. 492/MENKES/PER/IV/2010. Apart from that, we also show findings of polluted well water and also provide solutions on how to care for wells. During material delivery activities, we use an educational and participatory approach with the main focus being the community. The result of this service activity is that the community in Poka Village has good knowledge regarding drinking water quality standards so that it is hoped that the community can apply them in their daily lives.